Two sides of the same coin: A qualitative exploration of experiential and perceptual factors which influence the clinical interaction between physicians and Anabolic-Androgenic Steroid using patients in the UK - Neha Prasad Ainsworth; Sam N Thrower; Andrea Petróczi (Elsevier, 2022)
Background: Patient-physician interactions involve complex interplays between patient and physician autonomy. This is intensified in stigmatised populations, such as anabolic-androgenic steroid (AAS) users. The current study investigated what factors influence clinical interactions between physicians and AAS users, thus providing a holistic understanding of the underlying dynamics. Methods: For this exploratory two-cohort qualitative study, UK-based physicians (n = 6) and AAS-users (n = 6) were recruited via purposive and snowball sampling. Data were collected using semi-structured interviews. These interviews were audio-recorded, transcribed verbatim, and inductively analysed using reflexive thematic analysis. Results: Six themes were identified for AAS-using patients (perceived bias and lack of clinical knowledge; perceived power imbalance; riskiness of disclosure; feeling misidentified; experiencing hostility and prejudice; and collaborative clinical interactions) and four for physicians (professional barriers: lack of knowledge, guidelines and resources; preconceptions and prior understandings; direct exposure influences clinical confidence; and professional role quandary). The overall picture suggests primary impactive factors involve stigma management techniques amongst AAS-using patients and coping with clinical uncertainty for physicians. Conclusions: Blurred lines between enabling versus management impact both the AAS-using patient and the physician. Greater clarity is required regarding what constitutes appropriate management. Further discussion is warranted about the role of physician and patient autonomy. Improving access to healthcare services and expertly guided AAS cessation, if necessary, are vital for effective harm-reduction.